2006
DOI: 10.1093/europace/eul117
|View full text |Cite
|
Sign up to set email alerts
|

Syncopal monomorphic ventricular tachycardia with pleomorphism, sensitive to antitachycardia pacing in a patient with Brugada syndrome

Abstract: Polymorphic ventricular tachycardia and ventricular fibrillation are the most common arrhythmias in Brugada syndrome, causing syncope or sudden death. Sustained monomorphic ventricular tachycardias are rare in this context. We report the case of a 41-year-old man with repetitive syncopal episodes and an ajmaline-induced characteristic Brugada ECG pattern, in whom episodes of monomorphic ventricular tachycardia with pleomorphism and response to ventricular pacing were documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Although life‐threatening arrhythmias and SCD in JWS are generally associated with slow heart rates, the potential therapeutic benefit for cardiac pacing at relatively fast rates remains largely unexplored …”
Section: Approaches To Therapy Of Jwsmentioning
confidence: 99%
“…Although life‐threatening arrhythmias and SCD in JWS are generally associated with slow heart rates, the potential therapeutic benefit for cardiac pacing at relatively fast rates remains largely unexplored …”
Section: Approaches To Therapy Of Jwsmentioning
confidence: 99%
“…18 It also has been demonstrated that standard ICD-EG morphology can accurately distinguish between 2 different sites of ventricular impulse formation as long as they are Ͼ2 cm apart. 19 Indeed, ICD-EG morphology has been used to distinguish between 2 different M-VTs in previous reports, such as in a patient with Brugada syndrome 30 or in patients with Chagas disease. 31 Although a …”
Section: Incidence Of Pl and MMmentioning
confidence: 99%
“…Identification of the putative VT(s) exit sites is a key step of substrate‐based ablation approaches for unstable VT(s), and requires detailed pace mapping along the scar edge to reproduce the morphology of the clinical VT(s) on 12‐lead ECG . However, in a substantial proportion of patients, the 12‐lead ECG of the clinical arrhythmia is not available and stored IEGMs of the clinical event can been used as a surrogate for 12‐lead ECG to identify the clinical VT(s) . In this regard, IEGM morphological analysis plays an important role, as other parameters, such as the VT cycle length, typically show a considerable overlap between the clinical VT and other inducible nonclinical arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, in a substantial proportion of patients, the 12-lead ECG of the clinical arrhythmia is not available and stored IEGMs of the clinical event can been used as a surrogate for 12-lead ECG to identify the clinical VT(s). 4,[7][8][9] In this regard, IEGM morphological analysis plays an important role, as other parameters, such as the VT cycle length, typically show a considerable overlap between the clinical VT and other inducible nonclinical arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation